Effectiveness of Multi-Matobe Integration in Social Studies Learning to Enhance Critical Thinking Skills - Rasimin Rasimin; Muh Zuhri; Muhammad Hamsah; Nurchamidah Nurchamidah; Ali Miftakhu Rosyad (Yayasan Keluarga Guru Mandiri, 2022)
This study aims to analyze the effectiveness of the Multi-Matobe learning strategy in enhancing elementary-school students' critical thinking skills. The research population was elementary school students in Salatiga, Indonesia. Using purposive sampling, 160 students were chosen as samples. The research has a Randomize Pretest-Posttest Control Group Design. Students' critical thinking skills are measured by a validated test containing real religious tolerance issues. Data were analyzed using Paired Samples t-test. The results showed that the integration of Multi-Matobe learning is effective in enhancing students' critical thinking skills. The contribution of this research is that students can think critically and have a tolerance to face global competition by integrating the Multi-Matobe strategy in schools.